Do R&D expenditures matter more than those of marketing to company performance? The moderating role of industry characteristics and investment density. Issue 2 (7th February 2016) - Chen, Ping-Chuan; Chan, Wu-Chiang; Hung, Shiu-Wan; Hsiang, Yi-Jung; Wu, Li-Chang
ABSTRACT: Confronting competitive environment, enterprises differentiate their product by promoting their R&D or marketing capacities. Scholars have verified that there is a direct relationship and a deferred effect between R&D expenditures and firm performance, but that there exists an inconsistency between marketing expenditures and firm performance. However, previous studies have neglected to analyse and compare the impact of corporate R&D and marketing investment on performance, and also ignored the moderating effects of different industry characteristics and investment densities. The study attempts to fill the gap by constructing a model to accommodate all these factors. The empirical results indicate that R&D and marketing expenditures have a positive impact on enterprise operating performance, and that there is a longer deferred effect in R&D expenditures than in marketing expenditures. By investing in R&D expenditures, manufacturing enterprises can increase their performance more than in service enterprises, and electronic enterprises can improve their performance compared with other types of firms. Finally, investments with higher R&D density can result in a higher performance.